COMPARATIVE EFFECT OF ALPHA TOCOPHEROL AND ASCORBIC ACID ON BODY WEIGHT OF RATS EXPOSED TO CHRONIC RESTRAINT STRESS - Moazzam, Sadia; Majeed, Farzana; Sattar, Rabia; Irfan, Asma; Mughal, Irfan Afzal (Pakistan Journal of Physiology, 2021)
Background: The stress is defined as the constellation of events, which begins with a stimulus, and subsequently results in the activation of certain physiologic systems. This study was planned to determine the comparative effect of ascorbic acid and alpha tocopherol on body weight of Sprague Dawley rats exposed to chronic restraint stress. Methods: This comparative experimental study was done in National Institute of Health (NIH), Islamabad. One-hundred-and-twenty male Sprague Dawley rats (mean weight 250±50 grams) were used and divided into 4 equal groups. Group I was taken as control. Group II was exposed to chronic stress, Group III was given only ascorbic acid prior to restraint stress, and Group IV was given only alpha tocopherol prior to restraint stress. Group III & IV were given prior supplementation of ascorbic acid, alpha tocopherol for 1 month. Results: There was a significant decrease in weight gain of rats exposed to the chronic stress as compared to control group. Individual supplementation with ascorbic acid and alpha tocopherol resulted in significant improvement of their eating habits with rats supplemented with ascorbic acid. Conclusion: Chronic stress has a detrimental effect on weight. This effect can be minimised by the intake of sufficient amount of antioxidants. Pak J Physiol 2021;17(4):8?10